Bilateral Chylothorax due to Disseminated Tuberculosis and Acute Lymphoblastic Leukemia in a young boy : A case report and Literature review - Anwar, Sayeeda; Rahman, AKM Matiur; Rahman, M Ekhlasur; Mollah, Md Abid Hossain; Matin, Abdul; Bilqis, Laila (Bangladesh Journal of Child Health, 2015)
Abstract not available DOI: http://dx.doi.org/10.3329/bjch.v38i3.22828 Bangladesh J Child Health 2014; VOL 38 (3) :164-168